GAMBARAN CITRA TUBUH PADA REMAJA PUTRI YANG MENGIKUTI KURSUS DI X MODELING - Herlinda Desi Anggraini; Muslimah Zahro Romas; Naila Nasywa (Jurnal Psikologi, 2024)
At the age of adolescence, individuals have several developmental tasks, one of which is the ability to accept physical conditions and be able to use their bodies effectively. This study aims to determine the body image of young women who take courses at X Modeling. This study used qualitative research methods. Collecting data in this study using the method of observation, interviews, and documentation. The subjects in this study were three young women aged 15-18 years who attended a course at X Modeling. The results of the research conducted showed that the three subjects had a positive body image based on aspects of body image and body image factors. Aspects of body image include appearance evaluation, appearance orientation, body area satisfaction, overweight preoccupation, body size categorization. Body image factors include mass media, family and interpersonal relationships.